Development of a framework and a tool for the assessment of water leakage in reinforced concrete buildings - Responde, Leomark C.
Being located in the tropics, the Philippines receives large amounts of precipitation. One inevitable disadvantage of such situation is the prevalence of water leakages manifesting inside buildings. These leakage cases are caused by several factors including hydraulic penetration into walls by wind driven rain, pressure differences, flawed fenestrations, defective drainage systems and often supplemented by faulty ventilation systems and leaky wall pipe systems. Water leakage inside building poses harm to the occupants and properties and affects the structure's serviceability, usability and contributes in the physical degradation of adjacent building components. The Philippines utilizes no uniform framework and tool in evaluating water leakages, without which the latter could not be properly assessed and remedial procedures could not be easily determined. This study thus proposes developing an evaluation framework and a corresponding tool based from international standards by selecting individual methodologies that will be applicable to the particular settings, conditions, technologies and local practices in the Philippines. This study will cover multi-story reinforced concrete buildings, defined as having a maximum of 4 stories and will not cover standards for repair.